Production of monoclonal antibody and development of an icELISA for the detection of paxilline in grain - Jiaxin Wang; Wenhua Shang; Shibei Shao; Jialin Zhang; Qiuyang Wu; Min He; Licai Ma; Jianzhong Shen; Zhanhui Wang; Kai Wen (Food and Agricultural Immunology)
Paxilline (PAX) is a tremorgenic mycotoxin that is thought to be associated with various syndromes in animals. To facilitate the determination of this toxin, a hapten was chemically synthesized and then respectively conjugated to Bovine Thyroglobulin (BTG) and Bovine serum albumin (BSA) for antibody production. Monoclonal antibody (mAb) 4F8 was finally obtained and used to establish an accurate and sensitive indirect competitive ELISA (icELISA). Various parameters that could impact the performance of icELISA were optimized, including the ion concentration, pH value and organic solvent. Under optimal condition, this assay exhibits an IC50 value as low as 0.84 µg L−1. The limit of detection (LOD) of the established icELISA method for PAX was 0.03–0.3 µg L−1. In conclusion, this study provided a rapid, sensitive, and high-throughput immunoassay for the detection of PAX in grains.